Hope and Distress Are Not Associated With the Brain Tumor Stage - Mayer, Simone; Fuchs, Stefanie; Fink, Madeleine; Schäffeler, Norbert; Zipfel, Stephan; Geiser, Franziska; Reichmann, Heinz; Falkenburger, Björn; Skardelly, Marco; Teufel, Martin (Frontiers in Psychology, 2021)
Objective: Hopelessness and depression are strongly associated with suicidality. Given that physical and psychological outcomes can be altered with hope, hope is a therapeutic goal of increasing importance in the treatment of brain tumor patients. Moreover, it is not yet understood which factors affect the perception of hope in brain tumor patients. In addition, it remains uncertain whether lower-grade brain tumor patients suffer less from psycho-oncological distress than higher-grade brain tumor patients. Methods: Neuro-oncological patients were examined perioperatively with the Distress Thermometer (DT) and the Herth Hope Index (HHI). In addition, psychological comorbidities (anxiety GAD-2, depression PHQ-2) and an assessment of general psycho-oncological distress were recorded. Results: Sixty-six brain tumor patients were included (median age 53 years, 35 % higher-grade brain tumors, i.e. WHO grade III/IV). No differences between higher- and lower-grade brain tumor patients were observed for general psycho-oncological distress and hope. However, higher-grade brain tumor patients showed a significantly higher level of depression (p ≤ .001) and more negative expectations regarding therapeutic success (H = 4.873, p ≤ .050). The extent of depression correlated negatively with hope. Conclusion: Unexpectedly, higher-grade brain tumor patients remained as hopeful as lower-grade brain tumor patients despite the devastating diagnosis, higher levels of depression, and a worse expectation of therapeutic success. Conversely, lower-grade brain tumor patients experience as much psycho-oncological distress as patients with a higher-grade brain tumor, underpinning the imperative need for comprehensive psycho-oncological screening. For all brain tumor patients, considering hope is important to avoid suicides resulting from hopelessness and depression.